Local Fractional Variational Iteration Transform Method for Solving Couple Helmholtz Equations within Local Fractional Operator - Jassim, Hassan Kamil (Sulaimani Journal for Pure and Applied Sciences, 2016)
In this paper, we investigate the solution of Helmholtz and coupled Helmholtz equations in two dimensional case, involving local fractional variation iteration method and Yang- Laplace transform which is called local fractional Variational iteration transform method (LFVITM). This method has Lagrange multiplier equal to -1, which makes the calculations more easily .The obtained result shows that the proposed method is efficient and accurate.
Keywords: Helmholtz equationCoupled HelmholtzEquation Localfractional variationaliteration methodYangLaplacetransform Localfractional operator